0492 Polygraphy+ With One EEG Channel Improves Osas Severity Classification. (27th April 2018) - Escourrou, P; Berthomier, C; Balekji, Z; Brandewinder, M; Berthomier, P; Piedvache, C; Agostini, H; Puisaix, N; Roisman, G
Abstract: Introduction: The Apnea-Hypopnea Index (AHI) determined by the ventilatory polygraphy (PG) has a limited validity due to the unknown duration of sleep and the non-consideration of the non-desaturating hypopneas followed by an arousal. This results in errors in determining the severity of OSAS in many patients. The aim was to compare the polysomnography (PSG) vs. a PG with the automatic analysis of an EEG channel (PG+). Methods: 25 patients (47 years, 12M, 33kg/m2) suspected of OSAS had an ambulatory PSG with a CID-LXe (Cidelec) equipped with an additional EEG (Cz-Pz) channel. The analysis was carried out blindly by 2 somnologists (S1, S2) in PG and then in PG+ on the periods of sleep determined by the automatic analysis algorithm of sleep/wake (S/W) and arousal detection ASEEGA (A) on CzPz and finally in polysomnography (PSG) as the reference, according to the AASM criteria. The epoch-by-epoch agreement of S/W scoring (concordance and Cohen kappa coefficient K) were calculated between PG+ and PSG. The classes of severity of AHI (<5, 5-14.9, 15-29.9, >30) by PG and PG+ were compared using the Friedman test. Sensitivity and specificity of PG and PG+ were computed for AHI thresholds of 15/hr and 30/hr in PSG. Results: The agreement computed by epochs for S/W scoring was 95% (K = 0.83) between S1 and S2 and 96% (K = 0.80) between A and the consensus of S1 and S2. AHI measured in PG: 24.2 ± 21.5, PG+: 29.4 ± 23.7 and PSG: 31.0 ± 24.6 were significantly different (p<0.0001). Classes of severity differed between PG and PSG (p<0.0001) but not between PG+ and PSG. Compared to PG, 4 (16%) patients had a higher severity in PG+ and PSG. Sensitivity of PG and PG+ was 87.9% and 94% respectively at a 15/H threshold and 68% and 96% respectively at a 30/h threshold. Specificity was 100% in all conditions. Conclusion: By automated S/W and arousal analysis, PG+ better determine the severity of SAS than PG. Support (If Any): CIDELEC, PHYSIP, RESMED.